Sterically Encumbered Coordination Sites. Iron(II) Complexes of Jäger‐type ligands with a Terphenyl Backbone. Issue 22 (3rd August 2021) - Dürrmann, Andreas; Hörner, Gerald; Wagner, Stefan; Breuning, Matthias; Weber, Birgit
Abstract: A Schiff base‐like ligand H2 L TerPh featuring a para ‐terphenyl backbone was synthesized and converted in two steps to an octahedral iron(II) coordination polymer with 1, 2‐bis‐(4‐pyridyl)‐ethylene as bridging ligand. Single crystal X‐ray structure analysis was possible for the free ligand and the two octahedral iron(II) complexes. The Schiff base‐like ligand features a [ N 2 O 2 ] 2− coordination sphere for the metal center and the para ‐terphenyl backbone introduces intrinsic steric constraint. Characterization of the coordination polymer with an N 4 O 2 coordination sphere around the iron center via magnetic measurements (SQUID) and room temperature Mössbauer spectroscopy revealed HS character in the entire temperature range investigated. Structure modelling with DFT calculations supports the findings, but support also the possibility of spin crossover in solution. Abstract :